Mentoring and Training in Developing Gunung Ireng Geotourism, Patuk District, Gunungkidul Regency, Yogyakarta Special Region - Sri Mulyaningsih; Dina Tania; Nurwidi Astanto Agus Tri Heriyadi; Suhartono Suhartono (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Gunung Ireng geosite is an excellent geoheritage that is also a part of the Gunungsewu UNESCO Global Geopark in Pengkok, Gunungkidul Regency. It is widely recognized as an experiential leisure tour destination with the sunrise, sunset, and milky way watching as its activities. The primary attraction is the natural museum of Tertiary submarine paleo-volcanic miniature that was developed during the Early Miocene (±20-23 million years ago). Mentoring in utilizing the resources is necessary. The local community has agreed to develop geotourism as an effort to conserve the cultural, biotic, and geological environment. The certified instructors or mentors and professionals used mentoring methods to increase the local community’s abilities in preparing, managing, and evaluating the geotourism, including management, advertisement, marketing, guidance, web hosting, culinary, and accommodations.. The results are the status of the geoheritage area (by the Ministry of Energy and Mineral Resources No. 13 K.HK.01.MEM.G.2021), the viral of the local Gunung Ireng’s Spot Festival, the local culinary facilities, the CHSE certificate, as well as up to 300% increase in visitors per month before the pandemic and 200-300% increase during the pandemic. Other results that have successfully developed the supporting attractions are the Ahad Pon traditional market, the footsteps flashback of the great da'wah Sunan Kalijogo on Gunung Ireng and the Geological Natural Track of the Ancient Volcano of Gunung Ireng. Those three attractions are the efforts to improve the local community's economy, nature, and cultural conservation as the solid implementations of geotourism activities. Qualitatively, these various efforts are now starting to show impacts, with the increased motivation of the community to focus more on developing this destination, and the increasing attention of local governments to support these conservation activities, although quantitatively it has not to be measured yet.